ANALISIS PENGARUH KUALITAS PRODUK, KESESUAIAN HARGA DAN INTENSITAS PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA MEREK ROKOK DJARUM SUPER (Studi kasus pada konsumen rokok Djarum Super di kota Semarang) - Maftuh Baedowi ZA, Mohammad; Lataruva, Eisha (Diponegoro Journal of Management, 2012)
The study analyze factor affecting consumers decision making purchasing. Independent variables are product quality (X1), price suitability (X2), and promotion intensity (X3). Dependent variable is purchase decision making in Djarum Super cigarette consumers in the city of Semarang (Y). Samples were 100 respondents takes by accidental sampling technique.The analytical using SPSS 13.0 the study condicted, reliability test, validity test, classic at asumption test. The results are :Y = 0,294 X1 + 0,360 X2 + 0,190X3. The determination coefficient (adjusted R2) is 0,473 or 47,3 percen this mean the model developed was good. Price suitability shows the biggest regression coefficient in the model. This implies price suitability is the most important factor affecting consumers purchase decision. The second important factor is product quality and then promotion intensity as the third factor affecting purchase decision.